The characteristic of hardness and microstructure of extraction forceps for dental and oral care made of stainless-steel - Kholis, Nur; Nuryanto, Nuryanto; Mustofa, Arif (Department of Mechanical Engineering Universitas Muhammadiyah Surakarta, 2020)
The reliability of medical devices such as extraction forceps is vital for dental and oral care. Apart from having hygienic properties, the extraction forceps must be strong and resistant to corrosion. This study evaluates the effects of tempering temperature on the hardness and microstructure of a medical device's material made from stainless-steel DIN 4021. In the experiments, a heat treatment process was carried out previously with a temperature of 1,050°C and a holding time of 20 minutes. A quenching process was conducted using a cooling channel that flowed with water at 10-20°C. After the heat treatment, the material was subjected to a tempering process with temperature variations of 200, 400, and 600°C. The research results indicated that the heat treatment process could increase the material's hardness value—the hardness value of the raw material changed from 20 to 48.67 HRC with the heat treatment. The tempering parameters resulted in the highest hardness value of 46.67 HRC at 200°C and the lowest value of 42.33 HRC at 600°C. Microstructure testing using optical microscopy showed that it produced ferrite, pearlite, and martensite structures. In contrast, the result of a microstructure testing using Scanning Electron Microscopy on the surface of the material is that the higher the tempering temperature, the larger the particles' area and dimension.